The Effects Of The Sprıng-Loaded Posterıor Bıte-Block On The Vertıcal Dımensıons Of The Face And The Dentoalveolar Structures - Hakan N. İşcan; Sevil Akkaya; Elçin Koralp (Galenos Yayinevi, 1991)
The aim of this study was to investigate the effects of the spring-loaded posterior bite-block on the vertical dimensions of the face and the dentoalveolar structures in subjects having skeletal and dental open-bite during the period of growth and development. The material of the present study was consisted of the lateral cephalometric and hand-wrist radiographs taken pnior to and at the end of the study from eleven open-bite subjects having a mean age of 10.297 years whose functional treatments towards open-bite malocclusion were involved by the help of spring-loaded posterior bite blocks within a mean period of 0.49±0.28 years and 12 control subjects with similar skeletal and dental characteristics having a mean age of 9.964 years who were observed for a mean period of 0.70±0.04 years. The results of the study exhibited decreases in the mandibular plane angle, lower and total anterior facial heights and the restraint of the upper posterior facial height as the effects of the spring loaded posterior bite-blocks. A restraint in the increase of posterior facial height was observed that can be related to the increase of the ramal inclination and the gonial angle. As the effects of the appliance on the dentoalveolar structures; the inhibition of the vertical grwth in the posterior regions especially in the upper, retrusion of the upper and lower incisors and the increase of the overbite were noticed.